Aplicación del Método REBA para reducir el riesgo disergonómico de los operarios de campo de la empresa Cartavio S.A.A. 2022 - Gamboa García, Robert Nilson Giussepe (2023)
The objective of this research is to apply the REBA method to reduce the disergonomic risk of the field operators of the company Cartavio S.A.A. For this, a descriptive study with an observational and cross-sectional design was achieved. With a non-probabilistic convenience sample of 6 workers. The technique used to determine the initial risk level was observation, interviews, documentary analysis and use of the field format to identify dysergonomic risks (REBA). As results, it was obtained that the level of disergonomic risk of the postures under analysis were 4 very high level (27%), 9 high level (60%) and 2 medium level (13%); In addition, it was identified that non-ergonomic risk factors were present in the activities, such as: repetitive movements, hand and wrist efforts, lifting loads when handling the tool, and postural changes. A new work standard is established by emphasizing the highest scores obtained from the REBA method; It was obtained that after taking the new standard, the level of disergonomic risk of the postures under analysis was: 9 medium level (60%), 5 low level (33%) and 1 negligible level (7%); It is concluded that after the application of the REBA method, the disergonomic risks will be needed, evidenced by the reduction of the sum of the initial score of the postures by 47%.